In vivo and molecular evaluation of artesunate+sulfadoxine-pyrimethamine efficacy for uncomplicated falciparum malaria in Tehama region, Yemen / Wahib Mohammed Mohsein Atroosh - Wahib Mohammed, Mohsein Atroosh (2017)
Yemen has updated its national malaria policies in 2009 to introduce histidine rich protein 2 – based rapid diagnostic test (HRP2-RDT) as a method of diagnosis in peripheral malaria-endemic areas, and to replace chloroquine (CQ) by artemisinin combination therapy (ACT) for treating uncomplicated falciparum malaria infection. The present study aimed to evaluate the HRP2-RDT and to assess the therapeutic efficacy of artesunate + sulfadoxine/pyrimethamine (AS+SP) as a first line treatment. A total of 622 febrile individuals from two malaria-endemic areas in Tehama region, Yemen (Hodeidah and Al-Mahwit governorates) were screened by CareStartTM malaria HRP2-RDT and confirmed later by microscopy, followed by gene sequencing analysis of Pfhrp2. Evaluation of AS+SP therapeutic efficacy was performed through in-vivo evaluation of the clinical and parasitological response over 28 days of follow-up according to standard protocols. Moreover, frequency of mutations associated with drugs resistance was obtained for the pfdhfr, pfdhps, and pfK13 genes for AS + SP, as well as pfcrt and pfmdr1 genes for other antimalarials. A total of 188 (30.2%) participants were found positive for P. falciparum by the RDT compared to 189 (30.4%) by microscopy. The sensitivity and specificity of the RDT were 90.5% and 96.1%, respectively. Eighty-six patients completed the AS+SP in-vivo study, with a cure rate of 96.5% (94.2% PCR-uncorrected). However, the efficacy of gametocyte clearance was poor, with gametocytes persisting throughout the study in some patients. All the isolates sequenced had the pfk13 propeller domain wild-type allele, and mutations associated with SP failure were observed only for pfdhfr, with the double mutation (S108N+N51I) was reported in 65.4% of the isolates. Pfcrt gene showed wide prevalence of mutations, with the predominance of pfcrt 76T CQ resistance (97.7%). Mutated pfcrt haplotypes were highly prevalent (98.8%) with CVIET classic, old-world African/Southeast Asian haplotype being the most predominant, and was mostly found in the isolates from Khamis Bani Saad and AdDahi districts (93.1% and 88.9% respectively). Interestingly, the SVMNT new-world South American haplotype was exclusively detected in isolates from Bajil districts of Hodeidah (9.3%). Mutations at Y184F of pfmdr1 were found at a fixation level (100%) in all districts, while mutations of codons 1034C and 86Y were only found in the isolates from AdDahi and Khamis Bani Saad districts. In conclusion, CareStartTM Malaria HRP2-based RDT showed high level of sensitivity and specificity in malaria-endemic areas in Yemen. Moreover, AS+SP therapy remains effective for the treatment of uncomplicated falciparum malaria iv with poor gametocidal activity. No polymorphism in pfk13 was detected in all isolates studied. Adding a single dose primaquine, which minimizes transmission potential, to the current ACT drug policy is strongly recommended. The high prevalence of mutations in pfcrt, 5 years after official cessation of CQ suggests a sustained CQ pressure on P. falciparum isolates in the study area. Moreover, the low prevalence of mutations in the pfmdr1 gene could be a good indicator of the high susceptibility of P. falciparum isolates to antimalarials other than CQ. Therefore, a new strategy to ensure the complete nationwide withdrawal of CQ from the private drug market is recommended.